2023
DOI: 10.3171/2022.5.jns22935
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral hemorrhage in vestibular schwannomas after stereotactic radiosurgery

Abstract: OBJECTIVE Vestibular schwannomas (VSs) are benign tumors of the cerebellopontine angle that are typically managed with stereotactic radiosurgery (SRS). Intratumoral hemorrhage (ITH) of VSs is a rare occurrence that results in worsening vestibular and new cranial nerve deficits. Few reports have described the management and outcomes of this entity after SRS. To further delineate the incidence and impact of this event, the authors performed a retrospective review of their VS SRS patients at a single center. ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…1,2 A recent study found a cumulative incidence of ITH of 0.26% (5 ITH of 1902 patients with VS) among patients with VS after stereotactic radiosurgery (SRS). 3 These results contrast with another series that found ITH cumulative incidence of 0.4% among newly diagnosed or observed (ie, wait and watch) VS. 4…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…1,2 A recent study found a cumulative incidence of ITH of 0.26% (5 ITH of 1902 patients with VS) among patients with VS after stereotactic radiosurgery (SRS). 3 These results contrast with another series that found ITH cumulative incidence of 0.4% among newly diagnosed or observed (ie, wait and watch) VS. 4…”
mentioning
confidence: 68%
“…stereotactic radiosurgery (SRS). 3 These results contrast with another series that found ITH cumulative incidence of 0.4% among newly diagnosed or observed (ie, wait and watch) VS. 4 While ITH in patients with VS who have had surgery or have been observed has been researched before, few reports have explored the incidence of ITH in VS after SRS. [4][5][6] Therefore, our multi-institutional study aims to describe ITH incidence, patient characteristics, management strategies, and clinical outcomes in patients with VS who underwent SRS.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Intratumoral hemorrhage in vestibular schwannomas is rare, with a reported incidence of 0.4% in general [ 3 ] and 0.26% after SRS [ 4 ]. It usually occurs 80 or 130 months after SRS [ 4 , 5 ]. Although the mechanism of intratumoral hemorrhage and the effects of the radiation are not completely understood, anticoagulation has been cited as a risk factor for intratumoral hemorrhage in vestibular schwannomas [ 3 ].…”
Section: Discussionmentioning
confidence: 99%